Cognitive emotion regulation and life satisfaction among students from Mainland China in Malaysian universities - Weidi, Zhou; JeeChing, Pang (Frontiers in Education, 2023)
This study investigates the relationship between cognitive emotion regulation and life satisfaction among students from Mainland China in Malaysian universities. It aims to determine the level of life satisfaction, the frequency of using cognitive emotion regulation, the correlation between the two variables, and the predictive factors of life satisfaction. Four hundred and ninety (490) participants were selected from 12 universities in Malaysia through random sampling; 102 for a pilot study and 388 for the final study. A quantitative research design was developed to conduct the investigation using two questionnaires; the Multidimensional Students’ Life Satisfaction Scale (MSLSS) and a Cognitive Emotion Regulation Questionnaire (CERQ). Data were analyzed using the statistical tools SPSS 26 and Smart PLS (SEM) 3.0. The findings showed that a high proportion of participants (72.4%) demonstrated a high level of life satisfaction among students from Mainland China in Malaysian universities and 48.7% of these students always used cognitive emotion regulation. 12.6% of students from Mainland China displayed a low level of life satisfaction and 13.4% rarely used cognitive emotion regulation. In conclusion, there was a significant relationship between cognitive emotion regulation and life satisfaction, in which positive reappraisal, positive refocusing, and refocusing on planning of cognitive emotion regulation had significant predictive powers for life satisfaction among students from Mainland China in Malaysian universities.